Publication Bias Among Conference Abstracts Reporting on Pediatric Quality Improvement Projects. (May 2020) - Tumin, Dmitry; Akpan, Uduak S.; Kohler, John A.; Uffman, Joshua C.
This study evaluated progress to publication of pediatric quality improvement (QI) projects initially presented as national conference abstracts, according to project findings and other characteristics. QI abstracts were identified among presentations at the 2010-2015 American Academy of Pediatrics National Conference & Exhibition, and publications were tracked through June 2018. Positive findings (improvement on at least 1 quantitative project outcome), interventions, and analyses were correlated with journal publication. Of 142 abstracts, 128 (90%) reported positive findings. Forty-nine positive abstracts and 3 abstracts reporting negative results resulted in publication (38% vs 21%, respectively; P = .256). Median time to publication was 1.2 years for projects with positive findings, compared to >3 years for abstracts with negative findings ( P = .029). Ninety percent of abstracts reported positive findings, and these abstracts progressed to publication more quickly. Overcoming publication bias for pediatric QI projects may enhance selection of promising interventions as new projects are designed.